Review of optimism, creativity and spirituality in tourism research - Garces, Soraia (2018)
Purpose - Optimism, creativity, and spirituality are important variables in Positive Psychology that can lead to better lives. The authors believe these are also fundamental concepts that can bring a new understanding of the tourism experiences, particularly in the current trend of the 'experience economy'. The study aimed to explore optimism, creativity, and spirituality from a Positive Psychology perspective on tourism settings to deepen the understanding of the state of the art and develop ideas for improvement of tourism research experiences Design - An extensive systematic literature review was developed anchored on PRISMA (2009) guidelines. The search engine Online Knowledge Library (B-On) was used and the search terms 'Optimism', 'Creativity' and 'Spirituality' crossed individually with 'Tourism', 'Travel' and 'Visitor'. In-depth analysis considering the chosen inclusion/exclusion criteria were undertaken concluding with a sample of 31 references. Findings - Overall, results showed a lack of optimism studies on tourism, leading to an urgent need to endeavor in the challenge of developing research. Creativity in tourism is mainly used as a background for the place and its culture and considers organizational, structural and product innovation development. Further, tourism can be seen as a spiritual activity seeking personal enrichment and fulfillment. Originality of the research - This study considers three variables not usually applied to tourism contexts as is clear by the low number of references found. The application of these and consequently of Positive Psychology on tourism is per se new, allowing the emergence of novel and important discussions on tourism.